THE CORRELATION OF HUSBAND SUPPORTS WITH COPING ON PRIMIGRAVIDA PREGNANT WOMEN IN PUSKESMAS PLERET BANTUL YOGYAKARTA 2018 - Wiwin Winarsih (Universitas Muhammadiyah Mataram, 2019)
Research Background: During their first pregnancy, most women find it difficult to manage their both physical and emotional disorders. Research objective: This research aims to investigate the counseling relationship between husband supports and coping on primigravida pregnant women during delivering their babies. Research methods: This research is an observation research applying the cross sectional design. The independent variable is husband supports; while the dependent variable is the coping on pimigravida pregnant women. Moreover, the population of this research involved all primigravida pregnant women in Puskesmas Pleret Bantul. The research sample consisted of ninety respondents. The data were collected by using questionnaires. The bivariate analysis was done by employing chi-square. Research findings: Primigravida women with adaptive coping come with the percentage of 45.5%. Primigravida women with their husband supports come with the percentage of 60%. There is a significant relationship (p<0.05) between husband supports and coping on prigrimavida pregnant women ((OR=3,7; CI95% 1,48-9,46)). There is a significant relationship between age (OR = 4.3; CI95% 1.33-14.3) and education (OR = 3.5; CI95% 1.25-9.99) and coping on prigrimavida pregnant women (p<0.05). Where as employment and economic status with coping in primigravida mother did not have a significant relationship. Conclusion: Husband supports improves adapting coping on primigravida pregnant women while giving birth.